Islamic Finance and Corporate Governance : Synergies for Sustainable Growth - Muhammad, Ali (Emerald Publishing Limited, 2025)
This book explores the various topics that create the intersection between three key areas of Islamic finance, corporate governance, and sustainable growth. The intersection between these areas develops a useful understanding of how Islamic finance and corporate governance is an essential aspect of sustainable growth. The book sheds light on the role of ethical investment such as environmental, social, and governance (ESG) in promoting sustainable goals. This book includes the debate on how social responsibility can be integrated into the Islamic banking framework for modern practices and ethical foundations. It also explores the governance mechanism in microfinance and Islamic banking institutions. Similarly, this book presents the governance framework, opportunities, and challenges related to Islamic fintech. The inclusion of Sukuk and Takaful governance frameworks in Islamic financial institutions is also included in the book. These areas are essential for the sustainable performance of Islamic finance. Additionally, the book also introduces a new direction within Islamic banking and corporate governance through Musharakah Mutanaqisah for elderly care, integrating financial literacy to ensure sustainable retirement. This topic can be a useful way to expand the boundaries of Islamic banking and corporate governance for sustainable performance. Lastly, it addresses strategic Zakat management to amplify social impact within corporate social responsibility, underscoring the importance of ethical and socially responsible practices in Islamic finance. Overall, this book provides a useful guide and innovative approaches for policymakers and managers to enhance their knowledge on various key topics of Islamic finance and corporate governance.